Genetic Biomakers: the Promising Tools in the Diagnosis and Manage of Headache Cases - Lopes, Thiago Luís Marques; Clarindo, José Fernando Muniz; Sousa, Arthur Vitor Couto de; Ferreira, Eduarda Lima Verde; Filho, Hildel Freire Leite (Headache Medicine, 2023)
Full abstract in PDF.